On some fixed point results for expansive mappings in S-metric spaces - Fetouci, Nora; Radenović, Stojan (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The aim of this paper is to establish some existence results of a fixed point for a class of expansive mappings defined on a complete S-metric space. Methods: An iteration scheme was used. Results: Some existing results of mappings satisfying contractive conditions are expanded to expansive ones, providing a new condition expressed in one variable under which the existence of a fixed point holds. Conclusion: This work provides new tools to fixed point theory together with their applications.